Aerodynamic study of the plane of training flight “KUNTUR” - Paín y Cols., Jhonatan (2019)
The present work realized in the facilities of the School of Officials and of the Service of Maintenance of the Air Force of Peru, located in the Air Base "Las Palmas" - Rut, with the aim to determine the aerodynamic response of the plane of training BD-4BP, known as "Kuntur", to the cruising speed of 174 MPH [1,2]. The Kuntur, it is a plane designed and constructed in Peru and possesses hybrid technology, there is for it the importance of developing this work. For the development of the present investigation the deductive methodology was applied, with which they could determine the vectors of speed and pressure concerning the plane, for it there used the computational software in dynamics of fluids - CFD "Fluent", which realizes a calculation based on the method of finite volumes [3,4]. Materials that were in use were, a personal computer Pentium IV with high speed of processing of information, the software CDF Fluent v6.2, models to scale and a tunnel of subsonic wind. The simulation is realized in 2D and first mesh the plane, for which the structures are defined and later there are placed the aerodynamic parameters (speed of plane, atmospheric pressure, viscosity of the fluid, number of Reynolds, type of flow, quantity of interactions), there being obtained by it values that after realizing the statistical treatment are presented in tables and graphs. The results presented in this work correspond to the simulation and show the profiles of speed and of pressure in the different points of the aircraft; this way also, the evaluations are realized to different angles of assault of the aircraft the turbulence being observed concerning the profile, concluding that the angle of assault does not exceed the 18 º that it enters loss. It is recommended to continue by the investigation in 3 dimensions, in order that it complements the design and performance of the plane of training Kuntur.